Smoothened/AMP-Activated Protein Kinase Signaling in Oligodendroglial Cell Maturation - Del Giovane, Alice; Russo, Mariagiovanna; Tirou, Linda; Faure, Hélène; Ruat, Martial; Balestri, Sonia; Sposato, Carola; Basoli, Francesco; Rainer, Alberto; Kassoussi, Abdelmoumen; Traiffort, Elisabeth; Ragnini-Wilson, Antonella (Frontiers in Cellular Neuroscience, 2022)
Abstract The regeneration of myelin is known to restore axonal conduction velocity after a demyelinating event. Remyelination failure in the central nervous system contributes to the severity and progression of demyelinating diseases such as multiple sclerosis. Remyelination is controlled by many signaling pathways including the Sonic hedgehog (Shh) pathway, as shown by the canonical activation of its key effector Smoothened (Smo), which increases the proliferation of oligodendrocyte precursor cells via the up-regulation of the transcription factor Gli1. On the other hand, the inhibition of Gli1 was also found to promote the recruitment of a subset of adult neural stem cells and their subsequent differentiation into oligodendrocytes. Since Smo is also able to transduce Shh signals via various non-canonical pathways including the blockade of Gli1, we addressed the potential of non-canonical Smo signaling to contribute to oligodendroglial cell maturation into myelinating cells using the non-canonical Smo agonist GSA-10, which downregulates Gli1. Using the Oli-neuM cell line, we show that GSA-10 promotes Gli2 upregulation, MBP and MAL/OPALIN expression via Smo/AMP-activated Protein Kinase (AMPK) signaling and also efficiently increases the number of axonal contact/ensheathment for each oligodendroglial cell. Moreover, GSA-10 promotes the recruitment and the differentiation of oligodendroglial progenitors into the demyelinated corpus callosum in vivo. Altogether, our data indicate that non-canonical signaling involving Smo/AMPK modulation and Gli1 downregulation promotes oligodendroglia maturation until axon engagement. Thus, GSA-10, by activating this signaling pathway, represents a novel potential remyelinating agent.